ENTERPRISE COMPETITIVENESS: EXPERIENCE OF THE DISTILLARY INDUSTRY - Mazur, Volodymyr; Mazur, Nataliia (Journal of European Economy, 2017)
The experience concerning provision of the enterprise competitiveness in the distillery industry is considered.